A QSPR approach to the ecotoxicity of ionic liquids (Vibrio fischeri) using VolSurf principal properties. Issue 4 (4th May 2016) - Paterno', Alessio; Scire, Salvatore; Musumarra, Giuseppe
Graphical Abstract: Abstract: Recently derived in silico structural descriptors for both IL cations and anions allowed the development of a QSPR model correlating ionic liquid structures to Vibrio fischeri toxicity using the partial least squares (PLS) approach. Interpretation of the PLS model confirmed the effect of IL cationic structural features such as the influence of cation side chain length, presence of heteroatoms, and non-aromaticity of the heterocyclic scaffold on toxicity. The PLS model also provided a quantitative evaluation of anion effects, previously not evidenced due to the structural similarity of the anions considered. A simple equation in which three descriptors (two for the cations and one for the anions) allow the prediction of Vibrio fischeri toxicity for over 8000 ILs is reported.